THE IMPORTANCE OF VALEOLOGY IN NURSING EDUCATION AND PRACTICE - Radjabova Markhabo Botirovna; Ruzieva Gulchekhra Atoevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Valeology, the science of health and healthy living, plays a vital role in the field of nursing. By emphasizing health promotion, disease prevention, and a holistic approach to patient care, valeology aligns closely with the goals of nursing practice. This article discusses the significance of integrating valeology into nursing education and practice, highlighting its contribution to improving public health and patient outcomes.